Blue-barred parrotfish Scarus ghobban Forsskål, 1775: is it a protogynous?. Issue 1 (May 2021) - Tresnati, J; Utari, D; Yasir, I; Aprianto, R; Rahmani, P Y; Yanti, A; Tuwo, A
Abstract: The blue-barred parrotfish Scarus ghobban is a reef fish that has not been a target fish in the past, but is now becoming a target fish. The blue-barred parrotfish is a monochromatic fish, so that the sex of individual cannot be identified based on secondary sexual characters. This research aimed to determine whether the blue-barred parrotfish is protogeny. The parameters observed were sex ratio, gonad maturity and size at first maturity. The sex ratio of Blue-barred parrotfish was not balanced. This study cannot reinforces the previous assumption that Blue-barred parrotfish was protogeny because the distribution of sex ratio related to the length class was dominated by males. This study cannot also reinforces the previous assumption that Blue-barred parrotfish is protogeny because the distribution of sex ratio related to the length class was dominated by males. The size at first maturity of the male Blue-barred parrotfish is 24.0 cm and the female is 31.6 cm. Small length class which was dominated by males, and size at first maturity of males which was smaller than females reinforces the assumption that Blue-barred parrotfish was not hermaphrodite protogynous, but dioecious. This is just a preliminary suspicion, more detailed studies are ongoing.